2010
DOI: 10.1111/j.1349-7006.2010.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S‐transferase A4 is a positive marker for rat hepatic foci induced by clofibrate and genotoxic carcinogens

Abstract: Peroxisome proliferators (PP), including clofibrate (CF), are nongenotoxic rodent carcinogens, and oxidative DNA damages are suggested as a causative event for carcinogenesis. Gene expression profiles differ between hepatic lesions induced by PP and genotoxic carcinogens. Our previous study revealed that expression of L-bifunctional enzyme (enoyl-CoA hydratase/3-hydroxyacyl-CoA dehydrogenase, BE) was repressed in preneoplastic lesions induced by PP, whereas it was enhanced in the surrounding tissues. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Immunohistochemistry revealed that GSTP1-1 was localized in preneoplastic foci and neoplastic tissues. GSTA4 was found to be strongly expressed in this case, and may be used as a positive marker for such lesions (Shimizu et al, 2010). Such GSTP1-positive single cells may be 'initiated cells', the DNA of which is modified with reactive metabolites derived from carcinogens in the first step of carcinogenesis (Satoh et al, 1989).…”
Section: Gstp1 Expressionmentioning
confidence: 71%
“…Immunohistochemistry revealed that GSTP1-1 was localized in preneoplastic foci and neoplastic tissues. GSTA4 was found to be strongly expressed in this case, and may be used as a positive marker for such lesions (Shimizu et al, 2010). Such GSTP1-positive single cells may be 'initiated cells', the DNA of which is modified with reactive metabolites derived from carcinogens in the first step of carcinogenesis (Satoh et al, 1989).…”
Section: Gstp1 Expressionmentioning
confidence: 71%
“…However, organic solvents, including acetone, has also been employed to fix tissues for some cases, in which milder fixation was suitable for downstream analyses, such as immunohistochemistry with specific antibodies [ 16 , 17 ]. Indeed, we have used acetone fixation for the immunohistochemistry of rat tissues [ 18 ]. Thus, we first examined whether DNA extracted from AFPE tissue specimens could be used for ORNi-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Rat livers were removed following the animal faculty guidelines. The livers were immediately stored at −80 °C or subjected to AFPE treatment as described previously [ 18 ]. DNA was extracted from frozen rat liver tissues (ca.…”
Section: Methodsmentioning
confidence: 99%
“…This study was performed at 8 weeks of CF administration, because our previous study revealed that preneoplastic foci lacking BE expression developed in sensitive KS‐type rats at this time‐point. ( 12,22 ) α‐SMA, CD68 and CD34 were used as markers for the HSC, Kupffer cell and sinusoidal endothelial cell, respectively, ( 21 ) and the numbers of cells positive for the respective marker were compared between the KS‐ and NC‐type rat livers. Individual staining results are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%